Genetic and Preventive Services for Hereditary Breast and Ovarian Cancer in the Czech Republic - Foretova, Lenka (BioMed Central, 2006)
The majority of hereditary breast and ovarian cancers can be accounted for by germline mutations in the BRCA1 and BRCA2 genes. Genetic counselling and testing in high-risk patients in the Czech Republic began in 1997 in two centres (Masaryk Memorial Cancer Institute in Brno, MMCI, and the General University Hospital plus the First Faculty of Medicine, Charles University in Prague, 1FMUK). Health insurance covers testing in MMCI, whereas testing at 1FMUK is covered by research grants. The spectrum of mutations in the BRCA1 gene is similar in the Bohemian (western) and Moravian (eastern) regions of the country but the mutation spectrum observed in the BRCA2 gene is completely different. There are three BRCA1 gene mutations that are responsible for 69% and 70.4% of all BRCA1 mutations identified in women reporting to the Brno and Prague centres, respectively. The two most frequent mutations in the BRCA2 gene, which comprises 41.5% of all detected BRCA2 mutations in Brno, were not found in women tested in the Prague centre. The testing of BRCA1/BRCA2 or other possible predisposition genes for hereditary breast/ovarian cancer is determined by medical geneticists after genetic counselling. Predictive testing is offered to persons older than 18 years of age. Genetic counselling centres are easily accessible to all inhabitants in the country. Specialized preventive care is mostly organized by MMCI and the General University Hospital in Prague; however, some patients and their family members are under the care of other oncology departments and clinics. The quality of preventive care in different hospitals is currently being investigated.